Anthology and Absence: The Post-9/11 Anthologizing Impulse - Lovering Rounds, Anne (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The decade after the attacks of 9/11 and the fall of the World Trade Center saw a proliferation of New York-themed literary anthologies from a wide range of publishers. With titles like Poetry After 9/11, Manhattan Sonnet, Poems of New York, Writing New York, and I Speak of the City, these texts variously reflect upon their own post-9/11 plurivocality as preservative, regenerative, and reconstructive. However, the work of such anthologies is more complex than filling with plurivocality the physical and emotional hole of Ground Zero. These regional collections operate on the dilemma of all anthologies: that between collecting and editing. Every anthology, and every anthologist, negotiates the relationship between what is present and what is missing. In light of some of the emerging and established scholarship on the history of the English-language anthology, this article reads closely the declarative paratexts and the silent but equally powerful canonical choices of several different post-9/11 poetry anthologies. In so doing, the article comes to suggest the ways the anthology’s necessary formal incorporation of absence and presence, rather than its plurivocality alone, connects collections of New York’s literature to the fraught discourse of memorialization and rebuilding at the site of the World Trade Center.